Evolution and trends in research on inclusive education: A bibliometric analysis and systematic review - Ríos, Cecilia Solís; Orellana, Sonnia Molina; Figueroa, Kenia Laz; Vera, Dinora Carpio (International Journal of Innovative Research and Scientific Studies, 2025)
Using a thorough bibliometric analysis, this study examines the development and patterns in inclusive education research during the previous 20 years. Since 2013, there has been a noticeable rise in scientific output, which is indicative of a heightened global emphasis on developing inclusive and accessible learning settings for all students. Even while the number of publications has increased significantly, the effect as indicated by citations has showed a mixed pattern, indicating that some recent studies have not yet attained the same degree of influence as older research. The analysis emphasizes the significance of a few major subjects that have dominated inclusive education research, including autism, assistive technology, and educational policies. Furthermore, the creation of inclusive policies and practices depends critically on a robust network of international cooperation, especially between scholars in the United States and Europe. Despite these advances, this study emphasizes the continued existence of important obstacles that prevent the successful application of inclusive education, including a lack of funding, inadequate teacher preparation, and institutional impediments. By highlighting areas that need more focus in order to keep moving forward toward more accessible and inclusive educational systems, this analysis offers a strong basis for future research.